MANFAAT EKOLOGIS AIR DALAM PERSPEKTIF AL-QUR’AN DAN SAINS PADA SEBUAH STUDI TAFSIR EKOLOGI - Muhammad Alvin (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
Water is a crucial element for human life and the stability of the earth's ecosystem. From the perspective of the Qur'an, water is not only considered as a source of physical life, but also as a manifestation of Allah's grace and power over all beings. This study explores the role of water in maintaining ecosystem sustainability and human health, as well as discussing the management of natural resources through innovative technologies such as desalination and wastewater purification. This article also examines the application of sustainability principles taught by the Qur'an in water management technology to ensure its sustainability. The findings of the study show that the importance of water goes beyond meeting physical needs; It has a deep spiritual dimension, which motivates humanity to value, preserve, and use water wisely and sustainably for the survival of future generations.